HAIR DYE-INDUCED RETINOPATHY MIMICKING MEK-INHIBITOR RETINOPATHY. Issue Volume 16:Issues 3(2022) (16th January 2020) - Faure, Céline; Salamé, Nabil; Cahuzac, Armelle; Mauget-Faÿsse, Martine; Scemama, Claire
Abstract : We report for the first time three cases of toxic retinopathy mimicking MEK-inhibitor retinopathy with bilateral posterior multiple serous detachment after using chemical hair dyes containing aromatic amines. Abstract : Purpose: To report a new toxic retinopathy related to the use of hair dye. Methods: Case reports of three patients with follow-up after exposure and until resolution. Results: There were three middle-aged women (32–66 year old) all of whom had bilateral moderate to severe vision loss and normal slit-lamp examination at presentation. Fundus examination showed bilateral multiple serous retinal detachments predominantly located in the posterior pole, with some pigment epithelial hypertrophy in chronic cases. Optical coherence tomography showed similar features as in MEK-inhibitor retinopathy. Electrooculogram performed in one patient showed abnormal Arden ratio. During follow-up, visual acuity improved with regression of the serous retinal detachments. The speed of resolution was proportional to the acuteness of the exposure to aromatic amines. Conclusion: Hair dyes containing aromatic amines can be responsible for bilateral toxic retinopathy mimicking MEK-inhibitor retinopathy.